2016
DOI: 10.1039/c5ee02433a
|View full text |Cite
|
Sign up to set email alerts
|

A novel cross-linked nano-coating for carbon dioxide capture

Abstract: Defect-free and cross-linked ultra-thin (sub 100 nm) film composite membranes have been prepared. The membrane materials formed exhibited significantly high CO2 permeances of over 1200 GPU as well as excellent CO2/N2 selectivity of over 40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 40 publications
2
87
1
1
Order By: Relevance
“…Besides, it was easy to change the viscosity of the PDMS solution based on the degree of crosslinking before the coating process. In several studies, different film PDMS membranes were successfully prepared, and they showed good CO 2 separation performances . For example, Merkel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was easy to change the viscosity of the PDMS solution based on the degree of crosslinking before the coating process. In several studies, different film PDMS membranes were successfully prepared, and they showed good CO 2 separation performances . For example, Merkel et al .…”
Section: Introductionmentioning
confidence: 99%
“…While CTA membranes prepared by the phase inversion technique do not have the ideal permeability for post combustion capture, their high CO 2 /N 2 selectivity, commercial readiness and proven industrial resilience means that they could have strong potential. Thin film composite CTA membranes have been prepared by other workers [8][9][10] and emerging membrane fabrication technologies such as layer by layer [11] and continuous assembly of polymers (CAP) [12] approaches could allow the thickness of the active layer to be reduced further, which would result in adequate permeance to meet gas flux requirements. Alternatively, the use of porous additives within the active layer to form a mixed matrix structure could also improve the permeability of the structure, without compromising the selectivity [13].…”
Section: Introductionmentioning
confidence: 99%
“…38 Fluorocarbon-based membranes have been prepared by such membrane preparation methods, which displayed a greater molecular sieving effect than those prepared by solution-diffusion separation. 50 Recently, Fu et al 51 developed an ultrathin ($100 nm) membrane with uniform thickness, which was able to facilitate high CO 2 transport (i.e., CO 2 permeance ¼ 1260 GPU and CO 2 /N 2 selectivity ¼ 43). This breakthrough was achieved by continuous assembly technology via atom transfer radical polymerization (ATRP) for defect-free thin-lm nanocomposites (TFC) based on cross-linked PDMS ultrathin dense layer (ca.…”
Section: Advances In Polymerization Of Ultrathin Lmsmentioning
confidence: 99%